PERBEDAAN KADAR HEMOGLOBIN PADA BAYI BARU LAHIR YANG DILAKUKAN PENUNDAAN PEMOTONGAN TALI PUSAT DENGAN YANG SEGERA DIPOTONG PADA PERSALINAN NORMAL DI RSUD GUNUNG JATI KOTA CIREBON PERIODE FEBRUARI - MARET 2014 - Endang Nurrochmi; Pepi Hapitria; Chaerunnisa Suhaemi (Care : Jurnal Ilmiah Ilmu Kesehatan, 2014)
Based on the 2010-2011 IDHS, the IMR in Indonesia is 35 per 1,000 live births. Despite infections that include respiratory tract infections and diarrhea, anemia is also one of the infant mortality causes in Indonesia, especially iron deficiency anemia. The incidence of anemia due to low hemoglobin levels in infants in Gunung Jati Hospital was by 7%. This study investigated the difference in hemoglobin levels in newborn infants with delayed cord cutting regarding hemoglobin levels in association with immediate umbilical cord cutting at normal deliveries in Gunung Jati Hospital of Cirebon from February to March 2014. The research method was quasi-experimental, with purposive sampling technique. The population was the entire woman with normal delivery uncomplicated by aterm gestational age in VK room. The number of samples was 60 people divided into two groups. The data were obtained from the direct observation of the respondents. From the results, the mean of the newborn hemoglobin levels prior to the umbilical cord cutting in the delayed and immediate groups was 16.51 and 16.16, respectively. The mean of newborn hemoglobin levels after cutting the umbilical cord in the delayed and immediate groups was 16.51 and 16.08, respectively. The mean of appropriate time to undertake cutting the umbilical cord of the newborn was to be delayed until the cord stopped pulsing